Genetically modified maize: Less drudgery for her, more maize for him?: Evidence from smallholder maize farmers in South Africa - Gouse, Marnus; Sengupta, Debdatta; Zambrano, Patricia; Falck-Zepeda, José B. (Elsevier, 2016)
Genetically modified (GM) crop technologies have made great strides since its first introduction in 1996. Although there is an extensive and growing body of literature on the economic impact of the adoption of GM crops in both developing and developed economies, there is only scant evidence that the technology has had any specific and distinguishable impact among female and male farmers. In economies where female farmers and female household members have a significant and often differentiated role in agriculture production, it is crucial to be able to answer this question. This paper presents quantitative and qualitative results from a study of the gender-specific adoption and performance effects of insect resistant (Bt) and herbicide-tolerant (HT) maize produced by smallholder farmers in the Kwa Zulu Natal province in South Africa. The findings indicate that women farmers value the labor-saving benefit of HT maize alongside the stacked varieties which offer both insect control and labor saving. Higher yields are the main reason behind male adoption, while female farmers tend to favor other aspects like taste, quality, and the ease of farming herbicide-tolerant (HT) crops. Women farmers (and also children) saved significant time because less weeding is required, an activity that has traditionally been the responsibility of female farmers. The newer stacked varieties were preferred by both male and female farmers and seemed to be in high demand by both groups. However, lack of GM seed availability in the region and poor market access were possible limitations to the adoption and spread of the technology.